The 5th Battalion of the Lithuanian Police (1941–1944) - Bubnys, Arūnas (Genocidas ir rezistencija, 2001)
This paper deals with the history of the 5th Battalion of the Lithuanian Police. It can be divided into several stages: a) the formation of the battalion and training in Kaunas (September-November 1941); b) service in the Pskov and Novgorod regions in Russia (December 1941-early 1944); c) service in Lithuania and Latvia (spring-autumn 1944). During all its time in service, the battalion guarded railways and military objects, and the Baltic coastline. Some companies served on the front line, were surrounded and fought Soviet partisans, though the losses were not heavy: several scores of troops were killed or wounded, some deserted. Unlike other Lithuanian police battalions, the 5th Battalion did not commit any war crimes and were not involved in killings of Jews and other civilians. The disbanding of the battalion was painful: seven troops were court martialed by the Nazis, 11 sent to hard labor camps and prisons; others were transferred to the 13th and 256th battalions. The Nazis did not resort to such drastic measures against any other Lithuanian police battalion.